Evaluation of Traditional Prognostic Factors for Stage I-III Colorectal Cancer Patients Who Survived for Over Five Years After Surgery - Luo, Dakui; Yang, Yufei; Shan, Zezhi; Liu, Qi; Cai, Sanjun; Li, Qingguo; Li, Xinxiang (Frontiers in Oncology, 2021)
The aim of this study was to explore the prognostic factors in stage I-III colorectal cancer (CRC) patients who had survived for over five years. A total of 9754 stage I-III CRC patients who received curative surgery in the Department of Colorectal Surgery, Fudan University Shanghai Cancer Center were enrolled in this study. Of them, 3640 patients had survived for over five years after surgery. Univariate and multivariate Cox regression analyses were performed in the entire cohort and those who had survived for over five years. Compared with patients in the entire cohort, patients who had survived for over five years were more likely to be younger, have less disease of signet ring cell histology, perineural invasion and vascular invasion, more well differentiated tumors, and stage I disease. In the entire cohort, increased age, signet ring cell, poor differentiation, more advanced pathological stage, perineural invasion and vascular invasion were inversely associated with disease-free survival (DFS) and overall survival (OS) using multivariable Cox regression analyses. Only age, pathological stage and perineural invasion remained significant in patients who had survived for over five years. Moreover, tumor location was an independent factor for OS in this subgroup. Predictors for prognosis of CRC change over time. Age, pathological stage and perineural invasion deserve more attention among patients who have survived for over five years.